Demographic and clinical characteristics of patients with type 1 diabetes mellitus: A multicenter registry study in Guangdong, China: 1型糖尿病患者的人口学及临床特征:中国广东的一项注册研究. (6th March 2016) - Yang, Daizhi; Deng, Hongrong; Luo, Guochun; Wu, Ge; Lin, Shaoda; Yuan, Lin; Xv, Meilun; Li, Shaoqing; Zhang, Xiuwei; Wu, Jianneng; Lang, Jiangming; Liang, Ganxiong; et al.
Abstract: Background: A lack of demographic and clinical data hinders efforts of health care providers in China to support patients with type 1 diabetes mellitus (T1D). Therefore, the aim of the present retrospective study was to provide an overview of the demographic and clinical characteristics of Chinese patients with T1D. Methods: Hospital medical records of patients with T1D (diagnosed between January 2000 and December 2011) in 105 secondary and tertiary hospitals across Guangdong province were reviewed. Data were collected on patient age at diagnosis, presentations at onset, physical examination, and diabetes management. Results: In all, 3173 patients diagnosed with T1D between January 2000 and December 2011 were included in the study (46.2% female). The median age at diagnosis was 27.5 years (interquartile range [IQR] 18.0–38.0) years and the median body mass index (BMI) at onset was 19.6 kg/m 2 (IQR 17.4–21.8 kg/m 2 ). Among adult patients, 0.9% were obese, 6.6% were overweight, 62.3% were normal weight, and 30.3 % were underweight. The prevalence of diabetic ketoacidosis (DKA) at onset was 50.1%. The proportion of patients with retinopathy, nephropathy, and neuropathy was 8.1%, 20.7 %, and 11.1%, respectively. Conclusion: The adult‐onset form of T1D is not rare in China. The registry participants were characterized by older age at onset, lower BMI, and a higher prevalence of DKA at onset compared with those in regions with a high incidence of T1D, such as northern Europe. These findings contribute to a better understanding of the heterogeneity of T1D in different populations and so will help healthcare providers to develop management models that are more suitable for these patients. Abstract : Distribution of age of onset of type 1 diabetes.